Giant Cell Arteritis: Updates and Controversies - Yu, Erin; Chang, Jessica R. (Frontiers in Ophthalmology, 2022)
Giant cell arteritis (GCA) is a systemic granulomatous vasculitis affecting the medium and large-size arteries, and may present with a range of ophthalmic findings. This review will cover GCA epidemiology, pathophysiology, clinical presentation, diagnostic workup, and treatment. Epidemiology and Pathophysiology: GCA is commonly found in elderly patients and individuals of Scandinavian descent. Recent publications suggest it may be more common in African Americans and Hispanics than previously thought. It is very rare in Asian and Middle-Eastern populations, and there is little data regarding African populations. Genetic studies have identified increased risk associated with HLA-DRB1*04. Rather than a response to a specific antigen such as varicella zoster virus, current immunology research suggests that GCA results from changes associated with the aging immune system. Clinical presentation to ophthalmology: Arteritic anterior ischemic optic neuropathy is the most common ophthalmic manifestation of GCA, but central or branch retinal artery occlusion, ophthalmic artery occlusion, cranial neuropathies causing diplopia, and more rarely anterior segment ischemia and anisocoria may also occur. Clinical testing including visual field testing, OCT, OCT-A, ICG and fluorescein angiography can be helpful in suggesting a diagnosis in addition to the clinical exam. Diagnostic Workup: GCA is ultimately a clinical diagnosis, but it is usually supported with lab results, pathology, and/or imaging. Temporal artery biopsy (TAB) remains the gold standard diagnostic test although its sensitivity is debated and practice patterns still vary with respect to sample length and whether unilateral or simultaneous bilateral biopsies are performed. Some studies have reported higher sensitivity of ultrasounds over TAB, with added benefits of time efficiency and cost effectiveness, promoting the diagnostic use of ultrasounds. MRI and even PET CT protocols offer additional options for less invasive diagnostic testing. Treatment: Vision-threatening GCA is treated acutely with emergent admission for intravenous methylprednisolone, and long-term high dose oral corticosteroids remain the standard of care, despite common and sometimes serious side effects. The use of steroid-sparing alternatives such as methotrexate and tocilizumab is becoming more common and additional agents are being investigated.